Entrepreneurship Learning System in Business Incubators : An Case Study In Indonesia - Famiola, Melia; Hartati, Sri (International Journal of Engineering and Technology, 2018)
This paper aims to explore the system of entrepreneurial learning in Indonesian business Incubator and identify their success factors to support the entrepreneurs. This study is qualitative research using case approach. We collect data from six incubators in West Java Indonesia and interviewing tenants and person in charge of the incubation management. In general, we found three similar stages of incubation assistance to encourage and support entrepreneurial process for their tenants: pre-incubation, incubation, and post-incubation. Even though the condition is not in an ideal, the respondents highlight some influent factors of the incubation performance in Indonesia; 1) government support for incubation program related in funding, infrastructure and policies toward the entrepreneurship ecosystem; 2) networking with financial institution; 3) Support from university and research centre; 4) Social environment of incubators.